Medium and long term runoff prediction method based on numerical rainfall forecast - WANG XIN; HUANG GUANGBIN; JIN LIN; XIE RUCHANG; LIN CHIA HUI; LIN CHUNKUN (2022)
The invention provides a medium and long term runoff prediction method based on numerical rainfall forecast, which is a product based on numerical rainfall forecast of the European mid-term weather forecast center in the future six months, is fused with a short term runoff forecast model, and greatly increases the forecast period of runoff forecast and the forecast precision of runoff forecast. 本发明提供一种基于数值降雨预报的中长期径流预测方法，是基于预测精度高的欧洲中期天气预报中心未来6个月的数值降雨预报产品，并融合了短期径流预报模型，大大的增加了径流预测的预见期和径流预测的预报精度。